Mechanistic PK-PD model of alendronate treatment of postmenopausal osteoporosis predicts bone site-specific response - Calvo-Gallego, José L.; Pivonka, Peter; Ruiz-Lozano, Rocío; Martínez-Reina, Javier (Frontiers in Bioengineering and Biotechnology, 2022)
Alendronate is the most widely used drug for postmenopausal osteoporosis (PMO). It inhibits bone resorption affecting osteoclasts. Pharmacokinetics (PK) and pharmacodynamics (PD) of alendronate have been widely studied, but few mathematical models exist to simulate its effect. In this work, we have developed a PK model for alendronate, valid for short- and long-term treatments, and a mechanistic PK-PD model for treatment of PMO to predict bone density gain (BDG) at hip and lumbar spine. According to our results, at least 3 compartments are required in the PK model to predict the effect of alendronate in both short- and long-terms. Clinical data of a 2-year treatment of alendronate, reproduced by our PK-PD model, demonstrate that bone response is site specific (hip: 7% BDG, lumbar spine: 4% BDG). We identified that this BDG is mainly due to an increase in tissue mineralization and a decrease in porosity. The difference in BDG between sites is linked to the different loading and a dependence of the released alendronate on the bone specific surface and porosity. Osteoclast population diminishes quickly within the first month of alendronate treatment. Osteoblast population lags behind, but also falls due to coupling of resorption and formation. Two dosing regimens were studied (70 mg weekly, 10 mg daily) and both showed very similar BDG evolution, indicating that alendronate accumulates quickly in bone and saturates. The proposed PK-PD model could provide a valuable tool to analyse the effect of alendronate and to design patient specific treatments, including drug combinations.